Urban Morphometrics and the Intangible Uniqueness of Tangible Heritage. An Evidence-Based Generative Design Experiment in Historical Kochi (IN) - Alessandro Venerandi; Ombretta Romice; Olga Chepelianskaia; Kavya Kalyan; Nitin Bhardwaj; Vija Viese; Sebastián Ugás; Shibu Raman; Sergio Porta (Heritage, 2021)
Asia is urbanising rapidly. Current urbanisation practices often compromise sustainability, prosperity, and local quality of life while context-sensitive alternatives show very limited impact. A third way is necessary to integrate mass-production, heritage, and human values. As part of UNICITI’s initiative, A Third Way of Building Asian Cities, we propose a scalable and replicable methodology which captures unique morphological traits of urban types (i.e., areas with homogenous urban form) to inform innovative large-scale and context-sensitive practices. We extract urban types from a large set of quantitative descriptors and provide a systematic way to generate figure-grounds aligned with such urban types. The application of the proposed methodology to Kochi (IN) reveals 24 distinct urban types with unique morphological features. Profiles, containing design-relevant values of morphometrics, are then produced for a selection of urban types located in the historical district of Fort Kochi/Mattancherry. Based on these, figure-ground design demonstrations are carried out in three sample sites. Outcomes seem aligned with the urban character of their respective types, while allowing distinct design expressions, suggesting that the proposed approach has potential to inform the design in historical/heritage areas and, more broadly, the search for a Third Way of Building Asian Cities.